Infrastructure and Economic Growth in the Middle East and North Africa - Um, Paul Noumba; Straub, Stephane; Vellutini, Charles (2012)
This paper analyzes the impact of infrastructure on growth of total factor productivity and per capita income, using both growth accounting techniques and cross-country growth regressions. The two econometric techniques yield some consistent and some different results. Regressions based in the growth accounting framework suggest that electricity production helps explain cross-country differences in total factor productivity growth in the Middle East and North Africa region. Growth regressions support that conclusion, while also stressing an effect of telecommunications infrastructure. Finally, growth regressions also indicate quite consistently that the returns to infrastructure have been lower in the Middle East and North Africa region than in developing countries as a whole.